Agradecimentos - Rosenfield, Kathrin; Santos, Alexandre; Tomm, Davi Alexandre; Mautone, Guilherme; Quadrado, Lauro Iglesias; Hoff, Patrícia Cristine; Trusz, Paula (Revista PHILIA | Filosofia, Literatura & Arte, 2020)
por Editores Seniores e Editores de Área